Elisabeth of Luxembourg (1409-1442) : A Hungarian Queen of the 15th Century - Dvořáková, Daniela, (East Central and Eastern Europe in the Middle Ages, 450-1450 ;, 2025)
This book is dedicated to an exceptional and almost forgotten figure of European medieval history, Queen Elisabeth of Luxembourg. Through the story of her life, the author of this volume examines one of the most dramatic periods of Hungarian medieval history (1437-1442), when after the death of Emperor Sigismund of Luxembourg, the kingdom lacked a strong monarch. Although the primary focus of this book is Queen Elisabeth, much attention is also paid to her husband, the Duke of Austria and the Roman-German King Albert II of Habsburg. The author reconstructs his short reign in the Kingdom of Hungary on the basis of hitherto unpublished sources, as well as Queen Elisabeth's struggle for the Hungarian crown, which she finally won at the cost of her own life. Through the inclusion of discussions on topics such as the status of women, hygiene, medicine, piety, and travel, the author sheds light not just on the details of Elisabeth's life, but also on life during this period of medieval history more generally.